A model for irritable bowel syndrome and anxiety comorbidities in relation to alcohol use disorders - Vashkevich, Katsiaryna; Janiuk, Kathryn; Maleki, Nasim (Frontiers in Medicine, 2023)
About 95% of human body serotonin synthesis occurs in the gastrointestinal tract (GI). Lack of sufficient serotonin levels is thought to play a key role in mood disorders, including anxiety disorders. In this study, we looked at a disorder affecting the GI tract, irritable bowel syndrome (IBS), and aimed to determine whether IBS is differentially associated with anxiety disorders in 252 chronic pain patients in the presence of a history of alcohol use disorders (AUD) given that alcohol is an extremely aggressive substance for the GI mucosa. We found that while the prevalence of IBS was not affected by the presence of AUD in chronic pain patients, IBS had significantly higher comorbidity with anxiety disorders in chronic pain patients with comorbid alcohol use disorders. We argue that these findings highlight mechanistic differences in the comorbidity of anxiety disorders with chronic pain and AUD, implicating a central role for GI problems stemming from chronic alcohol use. The findings may have important implications for the treatment of IBS patients with AUD who commonly present with anxiety disorders which could motivate the continuation of problematic drinking and impede recovery success. We propose that addressing GI problems in patients with AUD may help manage AUD and recovery more effectively.